Direct target and non-target analysis of urban aerosol sample extracts using atmospheric pressure photoionisation high-resolution mass spectrometry. (June 2019) - Giorio, Chiara; Bortolini, Claudio; Kourtchev, Ivan; Tapparo, Andrea; Bogialli, Sara; Kalberer, Markus
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous atmospheric pollutants of high concern for public health. In the atmosphere they undergo oxidation, mainly through reactions with ·OH and NOx to produce nitro- and oxygenated (oxy-) derivatives. In this study, we developed a new method for the detection of particle-bound PAHs, nitro-PAHs and oxy-PAHs using direct infusion into an atmospheric pressure photoionisation high-resolution mass spectrometer (APPI-HRMS). Method optimisation was done by testing different source temperatures, gas flow rates, mobile phases and dopants. Samples were extracted with methanol, concentrated by evaporation and directly infused in the APPI source after adding toluene as dopant. Acquisition was performed in both polarity modes. The method was applied to target analysis of seasonal PM2.5 samples from an urban background site in Padua (Italy), in the Po Valley, in which a series of PAHs, nitro- and oxy-PAHs were detected. APPI-HRMS was then used for non-target analysis of seasonal PM2.5 samples and results compared with nano-electrospray ionisation (nanoESI) HRMS. The results showed that, when samples were characterised by highly oxidised organic compounds, including S-containing compounds, like in summer samples, APPI did not bring any additional information with respect to nanoESI in negative polarity (nanoESI(-)). Conversely, for winter samples, APPI(-) could detect a series of aromatic and poly-aromatic compounds, mainly oxidised and nitrogenated aromatics, that were not otherwise detected with nanoESI. Highlights: Determination of particle-bound PAHs, nitro-PAHs and oxy-PAHs in PM2.5 samples. Comparison between nanoESI and APPI sources in HRMS. Automatic data processing scheme for both nanoESI and APPI-HRMS data. APPI did not add information for highly oxidised organic compounds compared to nanoESI. APPI(-) can highlight oxidised and nitrogenated PAHs better than nanoESI.